Preparation method of multipurpose nano-material composite film

Through the modification and functional gradient construction of cellulose nanofibers, combined with laser microprocessing and the application of hydrophobic materials, a multi-purpose nanomaterial composite film is formed, solving the problem that traditional composite films are difficult to meet multiple performance requirements, and achieving the versatility and high performance stability of composite films.

CN119529346APending Publication Date: 2025-02-28MAOMING GREEN CHEMICAL RESEARCH INSTITUTE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411813985.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional nanomaterial composite membranes are difficult to meet multiple performance needs in complex environments at the same time. For example, antibacterial, breathable and biocompatibility are required in the medical field, and self-cleaning, high filtration efficiency and weather resistance are required in the environmental protection field.

Method used

The cellulose nanofibers are initially grafted and modified through benzophenone derivatives, and the preset functional groups are introduced for deep modification, forming a composite layer with a functional gradient, and a micro-nano structure is formed through laser micro-machining technology, locally coated with hydrophobic materials, and finally forming a composite film by low-temperature ultraviolet curing or plasma-assisted curing, and additives are introduced on the surface or inside for uniform dispersion.

Benefits of technology

It improves the dispersion of nanomaterials and the grafting efficiency of functional groups, so that the composite membrane can enhance various functional characteristics such as antibacterial, antifouling, ultraviolet shielding, etc. on the basis of maintaining the original excellent performance, and realizes directional water guidance and self-cleaning functions, enhancing mechanical properties and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529346A_ABST
    Figure CN119529346A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of composite membranes, and discloses a preparation method of a multipurpose nano-material composite membrane, which comprises the following steps: firstly, carrying out preliminary grafting modification on cellulose nanofibers by using a benzophenone derivative to improve the dispersity, and then introducing a preset functional group to carry out deep modification to obtain a modified cellulose nanofiber composite membrane; the mass ratio of the cellulose nanofiber to the benzophenone derivative is (1: 0.05)-(1: 0.2); according to the invention, the dispersity of the nano material and the grafting efficiency of the functional group are effectively improved by finely regulating and controlling the modification process of the nano material, so that the composite film further enhances the multiple functional characteristics of antibacterial property, antifouling property, ultraviolet shielding property and the like on the basis of keeping the original excellent properties; and meanwhile, the construction of the functional gradient ensures that the composite film can exert the optimal performance in different application scenes, interface defects are not easily generated among the functional layers, and the overall performance is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite film preparation, and in particular relates to a method for preparing a multi-purpose nano material composite film. Background Art

[0002] With the rapid development of nanotechnology, nanomaterials have shown great application potential in many fields due to their unique physical and chemical properties. However, the preparation methods of traditional nanomaterial composite membranes often focus on the realization of a single function, and it is difficult to simultaneously meet the multiple performance requirements in complex environments. For example, in the medical field, composite membranes need to have multiple properties such as antibacterial, breathable and biocompatible; in the field of environmental protection, composite membranes are required to have self-cleaning, high filtration efficiency and weather resistance.

[0003] At present, although some studies have attempted to improve the performance of composite membranes by modifying nanomaterials, constructing functional gradients or designing micro-nano structures, these methods often have the following shortcomings: First, the modification process is complicated and difficult to control precisely, resulting in poor dispersion of nanomaterials and low efficiency of functional group grafting; second, the construction of functional gradients lacks a systematic design, and interface defects are easily generated between functional layers, affecting the overall performance; third, the design of the micro-nano structure is single, making it difficult to achieve advanced functions such as directional water conduction and self-cleaning; fourth, the introduction of additives is uneven, resulting in reduced functional efficiency and affecting the long-term stability of the composite membrane.

[0004] Therefore, a method for preparing a multi-purpose nanomaterial composite membrane is proposed to solve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a multi-purpose nanomaterial composite membrane to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a multi-purpose nanomaterial composite film, comprising the following steps: S1: First, the cellulose nanofibers are preliminarily grafted with benzophenone derivatives to improve the dispersibility, and then the preset functional groups are introduced for deep modification to give the nanomaterials multiple functional properties. The mass ratio of cellulose nanofibers to benzophenone derivatives is 1:0.05 to 1:0.2.

[0007] S2: preparing nanomaterial slurry, controlling the content of nanomaterial and the ratio of modifier in the slurry in different regions, forming a composite layer with a functional gradient, and setting the mass ratio of nanomaterial to adhesive in different regions to 1:0.8 to 1:1.5; S3: Forming micro-nano structures on the surface of the substrate by laser micromachining technology, and then locally coating these structures with hydrophobic materials to form hydrophobic microstructures with directional water conduction or self-cleaning functions. The coating amount of the hydrophobic material is 5-20 grams per square meter of the substrate; S4: coating according to preset gradient parameters and microstructure layout on the substrate; S5: forming a composite film by low temperature ultraviolet curing or plasma assisted curing; S6: Introduce additives on the surface or inside of the composite membrane and evenly disperse the additives through nano-encapsulation or in-situ polymerization.

[0008] Preferably, the S1 specifically comprises the steps of: S11: dispersing the cellulose nanofibers in a suitable amount of solvent to form a stable cellulose nanofiber suspension; S12: dissolving the benzophenone derivative in another solvent, ensuring that it is completely dissolved, and then slowly dropping it into the cellulose nanofiber suspension; S13: reacting under stirring conditions, controlling the reaction temperature and time, so that the benzophenone derivative is grafted onto the surface of the cellulose nanofibers through a chemical reaction; S14: after the reaction is completed, removing the unreacted benzophenone derivative and the solvent through a preset step to obtain a preliminarily modified cellulose nanofiber; S15: dispersing the initially modified cellulose nanofibers in a solvent again to form a suspension; S16: selecting a corresponding functional precursor compound according to the preset functional group to be introduced; S17: dissolving the functional precursor compound in a suitable solvent and slowly dropping it into the cellulose nanofiber suspension; S18: reacting under preset conditions, so that the preset functional groups are grafted onto the surface of the cellulose nanofibers through chemical reaction, thereby forming deeply modified cellulose nanofibers.

[0009] S19: removing unreacted substances through a preset step to obtain a final modified nanomaterial; S110: adding a cross-linking agent and performing heat treatment to enhance the interaction between the modified nanofibers.

[0010] Preferably, the S2 specifically comprises the steps of: S21: preparing nanomaterial suspensions of different concentrations according to the desired functional gradient; S22: dissolving an environmentally friendly water-based polyurethane adhesive in a solvent in a certain proportion to form an adhesive solution; S23: mixing nanomaterial suspensions of different concentrations with the binder solution respectively, and uniformly dispersing the nanomaterials in the binder by stirring to form nanomaterial slurries of different concentrations; S24: designing the order and area of ​​slurry coating according to the preset gradient parameters; S25: Using a coating device or a template, slurries of different concentrations are sequentially coated on a substrate to form a composite layer with a functional gradient.

[0011] Preferably, the S3 specifically includes: S31: Clean the substrate to remove oil, dust and impurities on the surface; S32: Perform drying treatment as needed to ensure that the surface of the substrate is dry and free of moisture.

[0012] S33: Use laser processing equipment to perform precise laser micro-processing on the surface of the substrate to form the desired micro-nano structure.

[0013] S34: Control laser parameters, including power, scanning speed, and frequency, to obtain microstructure morphology and size; S35: The hydrophobic material is dissolved or dispersed in a suitable solvent to form a hydrophobic coating; S36: locally coating the hydrophobic coating liquid on the microstructure of the substrate using a coating device; S37: Control the coating amount so that the hydrophobic material forms a uniform covering layer on the microstructure.

[0014] Preferably, the S4 specifically comprises the steps of: S41: Writing a coating program according to preset gradient parameters and microstructure layout on the substrate.

[0015] S42: placing the substrate on a working table of the coating equipment and performing positioning calibration; S43: starting the coating device and performing the coating operation according to a preset program; S44: coating the nanomaterial slurry according to a preset gradient and position.

[0016] Preferably, the S5 specifically comprises the steps of: S51: Select low-temperature UV curing or plasma-assisted curing equipment, and perform preheating and debugging; S52: Set the light intensity and curing time as needed; S53: sending the substrate coated with the nanomaterial slurry into a curing device; S54: Start the curing equipment and perform the curing operation according to the preset parameters.

[0017] Preferably, the S6 specifically comprises the steps of: S61: Select additives based on the required functional strength and overall performance requirements of the composite membrane; S62: dissolving or dispersing the additive in a solvent to form an additive solution; S63: Using nano-encapsulation or in-situ polymerization, the additives are uniformly introduced into the surface or inside of the composite membrane; S64: performing subsequent treatment on the composite membrane after the additive is introduced, including cleaning and drying; S67: Test various performance indicators of composite membranes, including antibacterial properties and ultraviolet absorption properties; Preferably, the preset functional groups include antibacterial groups and photosensitizing groups.

[0018] Preferably, the additives include antibacterial agents and ultraviolet absorbers, and the additives do not exceed 5% of the total mass of the composite film.

[0019] Preferably, the pre-set steps include centrifugation, washing and drying.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention effectively improves the dispersibility of nanomaterials and the grafting efficiency of functional groups by finely regulating the modification process of nanomaterials, so that the composite membrane further enhances its various functional properties such as antibacterial, antifouling, and ultraviolet shielding while maintaining its original excellent performance. At the same time, the construction of functional gradient ensures that the composite membrane can exert its optimal performance in different application scenarios, and interface defects are not easy to occur between the functional layers, which will not affect the overall performance; it is easy to achieve directional water conduction and self-cleaning functions. In addition, the introduction of a cross-linking agent for heat treatment not only enhances the bonding strength between the modified nanofibers, but also improves the overall mechanical properties and durability of the composite membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] See also Figure 1 As shown, the present invention provides the following technical solutions: Example

[0024] A method for preparing a multi-purpose nanomaterial composite film comprises the following steps: S1: First, the cellulose nanofibers are preliminarily grafted with benzophenone derivatives to improve the dispersibility, and then the preset functional groups are introduced for deep modification to give the nanomaterials multiple functional properties. The mass ratio of cellulose nanofibers to benzophenone derivatives is 1:0.05 to 1:0.2.

[0025] S2: preparing nanomaterial slurry, controlling the content of nanomaterial and the ratio of modifier in the slurry in different regions, forming a composite layer with a functional gradient, and setting the mass ratio of nanomaterial to adhesive in different regions to 1:0.8 to 1:1.5; S3: Forming micro-nano structures on the surface of the substrate by laser micromachining technology, and then locally coating these structures with hydrophobic materials to form hydrophobic microstructures with directional water conduction or self-cleaning functions. The coating amount of the hydrophobic material is 5-20 grams per square meter of the substrate; S4: coating according to preset gradient parameters and microstructure layout on the substrate; S5: forming a composite film by low temperature ultraviolet curing or plasma assisted curing; S6: Introduce additives on the surface or inside of the composite membrane and evenly disperse the additives through nano-encapsulation or in-situ polymerization.

[0026] In addition, in the present invention, regarding the above S1: the S1 specifically includes the steps of: S11: dispersing the cellulose nanofibers in a suitable amount of solvent to form a stable cellulose nanofiber suspension; S12: dissolving the benzophenone derivative in another solvent, ensuring that it is completely dissolved, and then slowly dropping it into the cellulose nanofiber suspension; S13: reacting under stirring conditions, controlling the reaction temperature and time, so that the benzophenone derivative is grafted onto the surface of the cellulose nanofibers through a chemical reaction; S14: after the reaction is completed, removing the unreacted benzophenone derivative and the solvent through a preset step to obtain a preliminarily modified cellulose nanofiber; S15: dispersing the initially modified cellulose nanofibers in a solvent again to form a suspension; S16: selecting a corresponding functional precursor compound according to the preset functional group to be introduced; S17: dissolving the functional precursor compound in a suitable solvent and slowly dropping it into the cellulose nanofiber suspension; S18: reacting under preset conditions, so that the preset functional groups are grafted onto the surface of the cellulose nanofibers through chemical reaction, thereby forming deeply modified cellulose nanofibers.

[0027] S19: removing unreacted substances through a preset step to obtain a final modified nanomaterial; S110: adding a cross-linking agent and performing heat treatment to enhance the interaction between the modified nanofibers.

[0028] In addition, in the present invention, regarding the above S2: the S2 specifically includes the steps of: S21: preparing nanomaterial suspensions of different concentrations according to the desired functional gradient; S22: dissolving an environmentally friendly water-based polyurethane adhesive in a solvent in a certain proportion to form an adhesive solution; S23: mixing nanomaterial suspensions of different concentrations with the binder solution respectively, and uniformly dispersing the nanomaterials in the binder by stirring to form nanomaterial slurries of different concentrations; S24: designing the order and area of ​​slurry coating according to the preset gradient parameters; S25: Using a coating device or a template, slurries of different concentrations are sequentially coated on a substrate to form a composite layer with a functional gradient.

[0029] In addition, in the present invention, regarding the above S3: the S3 specifically includes: S31: Clean the substrate to remove oil, dust and impurities on the surface; S32: Perform drying treatment as needed to ensure that the surface of the substrate is dry and free of moisture.

[0030] S33: Use laser processing equipment to perform precise laser micro-processing on the surface of the substrate to form the desired micro-nano structure.

[0031] S34: Control laser parameters, including power, scanning speed, and frequency, to obtain microstructure morphology and size; S35: The hydrophobic material is dissolved or dispersed in a suitable solvent to form a hydrophobic coating; S36: locally coating the hydrophobic coating liquid on the microstructure of the substrate using a coating device; S37: Control the coating amount so that the hydrophobic material forms a uniform covering layer on the microstructure.

[0032] In addition, in the present invention, regarding the above S4: the S4 specifically includes the steps of: S41: Writing a coating program according to preset gradient parameters and microstructure layout on the substrate.

[0033] S42: placing the substrate on a working table of the coating equipment and performing positioning calibration; S43: starting the coating device and performing the coating operation according to a preset program; S44: coating the nanomaterial slurry according to a preset gradient and position.

[0034] In addition, in the present invention, regarding the above S5: the S5 specifically includes the steps of: S51: Select low-temperature UV curing or plasma-assisted curing equipment, and perform preheating and debugging; S52: Set the light intensity and curing time as needed; S53: sending the substrate coated with the nanomaterial slurry into a curing device; S54: Start the curing equipment and perform the curing operation according to the preset parameters.

[0035] In addition, in the present invention, regarding the above S6: the S6 specifically includes the steps of: S61: Select additives based on the required functional strength and overall performance requirements of the composite membrane; S62: dissolving or dispersing the additive in a solvent to form an additive solution; S63: Using nano-encapsulation or in-situ polymerization, the additives are uniformly introduced into the surface or inside of the composite membrane; S64: performing subsequent treatment on the composite membrane after the additive is introduced, including cleaning and drying; S67: Test various performance indicators of composite membranes, including antibacterial properties and ultraviolet absorption properties; In addition, in the present invention, regarding the above-mentioned preset functional groups: the preset functional groups include antibacterial groups and photosensitizing groups.

[0036] In addition, in the present invention, regarding the above-mentioned additives: the additives include antibacterial agents and ultraviolet absorbers, and the additives do not exceed 5% of the total mass of the composite film.

[0037] In addition, in the present invention, regarding the above-mentioned preset steps: the preset steps include centrifugation, washing and drying Example

[0038] A1: Selecting cellulose nanofibers and benzophenone derivatives in a mass ratio of 1:0.1; In steps S11 to S19, benzophenone derivatives are grafted onto cellulose nanofibers, and then silver ion antibacterial groups are introduced for deep modification; An appropriate amount of glutaraldehyde was added as a cross-linking agent, and heat treatment was performed at 80 °C to enhance the interaction between fibers.

[0039] A2: Prepare three nanomaterial suspensions with different concentrations and mix them with environmentally friendly water-based polyurethane adhesive in a 1:1 ratio to form gradient slurries.

[0040] In the order of low concentration to high concentration, they are coated on the PET substrate in sequence to form a composite layer with gradually enhanced antibacterial properties.

[0041] A3: Micro-nano structures were processed on PET substrates by femtosecond laser. The laser power was set to 10W and the scanning speed was 100mm / s.

[0042] The fluorinated polymer hydrophobic material was dissolved in ethanol with a coating amount of 10 grams per square meter and only coated on the microstructure to achieve the self-cleaning function.

[0043] The coating, curing and additive introduction were carried out according to the steps S4 to S6 in Example 1.

[0044] The additives are selected from nano silver particles and ultraviolet absorbers, and the total added amount does not exceed 3% of the total mass of the composite film. Example

[0045] B1: The mass ratio of cellulose nanofibers to benzophenone derivatives was set at 1:0.08 According to steps S11 to S19 of Examples, in addition to introducing antibacterial groups, TiO2 photosensitive groups are also introduced to enhance the ultraviolet shielding ability.

[0046] B2: Two concentrations of nanomaterial suspensions were prepared and mixed with an environmentally friendly waterborne polyurethane adhesive at a ratio of 1:0.8 and 1:1.2; The coating sequence is designed to be low-concentration layer inside and high-concentration layer outside, forming a composite layer with different internal and external functions; B3: Use laser to process microlens array structure on PC substrate to increase light transmittance; No additional hydrophobic coating is required because TiO2 itself has a certain self-cleaning ability; Coating, curing and additive introduction were performed according to the steps of Example 1S4 to S6; The additive is a UV absorber, and the added amount is 2% of the total weight of the composite film. Example

[0047] Step C1: The mass ratio of cellulose nanofibers to benzophenone derivatives was adjusted to 1:0.15; During deep modification, quaternary ammonium salt antibacterial groups are mainly introduced to ensure high antibacterial performance.

[0048] C2: Prepare two concentrations of nanomaterial suspension and mix them with medical grade polyurethane adhesive in a 1:1 ratio; The slurry coating is designed to be uniform in thickness, but the concentration of nanomaterials in different areas is controlled to form a weak antibacterial gradient; C3: Using picosecond laser to process nanopore structure on medical-grade nonwoven substrate to increase breathability.

[0049] No additional hydrophobic coating is required, and the original hydrophilicity of the substrate is maintained.

[0050] The coating, curing and additive introduction were carried out according to the steps S4 to S6 in Example 1.

[0051] Nano-silver particles are selected as the additive, and the added amount is 1% of the total mass of the composite film to ensure the antibacterial effect within a safe range. Example

[0052] D1: cellulose nanofibers and benzophenone derivatives were selected at a mass ratio of 1:0.1 for preliminary grafting; During the deep modification stage, thermosensitive poly (N-isopropylacrylamide) (PNIPAAm) groups were introduced to make the nanomaterials temperature-responsive.

[0053] D2: Prepare a uniform concentration of nanomaterial suspension and mix it with the smart waterborne polyurethane adhesive in a 1:1 ratio to form a temperature-sensitive slurry.

[0054] When coating, ensure uniform thickness across the entire composite layer to maintain consistent temperature control.

[0055] D3: No additional laser micromachining is performed and the substrate surface is kept smooth to reduce the impact on the temperature response performance.

[0056] Optionally, a thin layer of transparent conductive material, such as ITO, is coated on one side of the composite film to cooperate with the intelligent temperature control system.

[0057] Coating, curing and additive incorporation were performed according to the standard procedures in Example 1.

[0058] The additive can be selected from materials that enhance the stability of the composite membrane, such as nano-silicon dioxide. Example

[0059] E1: After the initial modification of cellulose nanofibers using benzophenone derivatives, a silane coupling agent was introduced for deep modification to improve the surface hydrophobicity and barrier properties of the nanomaterials; E2: Prepare a high-concentration nanomaterial suspension and mix it with a polymer barrier resin (such as ethylene-vinyl alcohol copolymer EVOH) at a ratio of 1:1.5 to form a high-barrier slurry; Through multi-layer co-extrusion coating technology, slurries of different concentrations are layered and coated on the substrate to form a multi-layer barrier structure.

[0060] E3: No laser micromachining is performed to maintain the smoothness of the composite film surface to maximize the barrier effect.

[0061] Curing, additive introduction and subsequent processing were carried out according to the standard procedures in Example 1.

[0062] The additive may be a plasticizer to improve the flexibility and processing properties of the composite film. Example

[0063] F1: After the initial grafting modification, pH-sensitive groups (such as carboxyl or amine) and photosensitive groups (such as azobenzene) are introduced to give the nanomaterials dual environmental responsiveness.

[0064] F2: Prepare multiple nanomaterial slurries with different concentrations and modifier ratios to form complex environmental response gradients.

[0065] Using precision coating technology, different slurries are coated on the substrate according to preset patterns to form a composite film with complex environmental responsiveness.

[0066] F3: Laser micromachining can be designed into patterns that match environmental responsiveness, such as microporous structures that open and close under different pH conditions. Example

[0067] G1: Cellulose nanofibers were selected as the substrate, and the benzophenone derivatives were initially grafted to improve their dispersibility and reactivity.

[0068] Subsequently, precursor compounds of conductive polymers (such as polypyrrole and polyaniline) are introduced for deep modification to make the nanofibers conductive.

[0069] G2: The modified conductive nanofibers are mixed with an appropriate amount of water-based polyurethane binder to form a conductive slurry.

[0070] The concentration and distribution of nanofibers in the slurry are controlled to balance electrical conductivity and air permeability.

[0071] G3: Form a tiny pore array on a flexible substrate (such as PET, PI) through laser micromachining technology.

[0072] Apply the conductive paste evenly on the substrate, ensuring that the vent holes are covered by the conductive layer but not completely blocked.

[0073] G4: Use low temperature UV curing technology to cure the conductive layer.

[0074] An additional protective layer may be applied to the composite membrane surface to improve wear resistance and water resistance. Example

[0075] H1: After the cellulose nanofibers are initially modified using benzophenone derivatives, the functional groups of natural antimicrobial agents (such as chitosan and nanosilver) are introduced for deep modification.

[0076] H2: Mix the modified antibacterial nanofibers with a degradable polymer binder (such as PLA, PBAT) to form an environmentally friendly antibacterial slurry.

[0077] The concentration of nanofibers in the slurry is adjusted according to packaging requirements to achieve the desired antibacterial effect.

[0078] H3: Apply the antimicrobial slurry evenly on food-grade substrates (such as paper, PLA film) by rolling or spraying.

[0079] H4: Add an appropriate amount of plasticizer to the slurry to improve the flexibility and processing properties of the film.

[0080] H5: Use natural air drying or low-temperature drying to solidify the slurry into a film.

[0081] The composite film is tested for its antimicrobial properties to ensure it meets food safety standards.

[0082] Embodiment 10: I1: Transparent cellulose nanofibers or titanium dioxide nanoparticles were selected as the substrate, and photosensitive TiO2 nanoparticles were introduced through the sol-gel method for deep modification.

[0083] I2: Mixing the modified photocatalytic nanoparticles with a transparent silicon-based binder to form a photocatalytic slurry with high transparency; The concentration and distribution of nanoparticles in the slurry are adjusted to optimize photocatalytic efficiency and light transmittance.

[0084] I3: Forming micro-nano structures on the surface of architectural glass by chemical etching or laser micromachining technology to increase the photocatalytic surface area; The photocatalytic slurry is evenly coated on the micro-nano structure on the glass surface using precision coating equipment.

[0085] I4: The slurry is cured into a film by ultraviolet irradiation or heat treatment.

[0086] The photocatalytic performance of the composite membrane was tested to ensure that it could effectively decompose pollutants in the air and had self-cleaning capabilities.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a multi-purpose nanomaterial composite film, characterized in that: The steps include: S1: First, cellulose nanofibers are preliminarily grafted with benzophenone derivatives to improve dispersibility, and then preset functional groups are introduced for deep modification to give the nanomaterials multiple functional properties. The mass ratio of cellulose nanofibers to benzophenone derivatives is 1:0.05 to 1:0.2; S2: preparing nanomaterial slurry, controlling the content of nanomaterial and the ratio of modifier in the slurry in different regions, forming a composite layer with a functional gradient, and setting the mass ratio of nanomaterial to adhesive in different regions to 1:0.8 to 1:1.5; S3: Forming micro-nano structures on the surface of the substrate by laser micromachining technology, and then locally coating these structures with hydrophobic materials to form hydrophobic microstructures with directional water conduction or self-cleaning functions. The coating amount of the hydrophobic material is 5-20 grams per square meter of the substrate; S4: coating according to preset gradient parameters and microstructure layout on the substrate; S5: forming a composite film by low temperature ultraviolet curing or plasma assisted curing; S6: Introduce additives on the surface or inside of the composite membrane and evenly disperse the additives through nano-encapsulation or in-situ polymerization.

2. The method for preparing a multi-purpose nanomaterial composite film according to claim 1, characterized in that: The S1 specifically comprises the steps of: S11: dispersing the cellulose nanofibers in a suitable amount of solvent to form a stable cellulose nanofiber suspension; S12: dissolving the benzophenone derivative in another solvent, ensuring that it is completely dissolved, and then slowly dropping it into the cellulose nanofiber suspension; S13: reacting under stirring conditions, controlling the reaction temperature and time, so that the benzophenone derivative is grafted onto the surface of the cellulose nanofibers through a chemical reaction; S14: after the reaction is completed, removing the unreacted benzophenone derivative and the solvent through a preset step to obtain a preliminarily modified cellulose nanofiber; S15: dispersing the initially modified cellulose nanofibers in a solvent again to form a suspension; S16: selecting a corresponding functional precursor compound according to the preset functional group to be introduced; S17: dissolving the functional precursor compound in a suitable solvent and slowly dropping it into the cellulose nanofiber suspension; S18: reacting under preset conditions, so that the preset functional groups are grafted onto the surface of the cellulose nanofibers through chemical reaction, thereby forming deeply modified cellulose nanofibers; S19: removing unreacted substances through a preset step to obtain a final modified nanomaterial; S110: adding a cross-linking agent and performing heat treatment to enhance the interaction between the modified nanofibers.

3. The method for preparing a multi-purpose nanomaterial composite film according to claim 1, characterized in that: The S2 specifically includes the steps of: S21: preparing nanomaterial suspensions of different concentrations according to the desired functional gradient; S22: dissolving an environmentally friendly water-based polyurethane adhesive in a solvent in a certain proportion to form an adhesive solution; S23: mixing nanomaterial suspensions of different concentrations with the binder solution respectively, and uniformly dispersing the nanomaterials in the binder by stirring to form nanomaterial slurries of different concentrations; S24: designing the order and area of ​​slurry coating according to the preset gradient parameters; S25: Using a coating device or a template, slurries of different concentrations are sequentially coated on a substrate to form a composite layer with a functional gradient.

4. The method for preparing a multi-purpose nanomaterial composite film according to claim 1, characterized in that: The S3 specifically includes: S31: Clean the substrate to remove oil, dust and impurities on the surface; S32: Perform drying treatment as needed to ensure that the surface of the substrate is dry and free of moisture; S33: Using laser processing equipment, precise laser micro-machining is performed on the surface of the substrate to form the desired micro-nano structure; S34: Control laser parameters, including power, scanning speed, and frequency, to obtain microstructure morphology and size; S35: The hydrophobic material is dissolved or dispersed in a suitable solvent to form a hydrophobic coating; S36: locally coating the hydrophobic coating liquid on the microstructure of the substrate using a coating device; S37: Control the coating amount so that the hydrophobic material forms a uniform covering layer on the microstructure.

5. The method for preparing a multi-purpose nanomaterial composite film according to claim 1, characterized in that: The S4 specifically comprises the steps of: S41: Writing a coating program according to preset gradient parameters and microstructure layout on the substrate; S42: placing the substrate on a working table of the coating equipment and performing positioning calibration; S43: starting the coating device and performing the coating operation according to a preset program; S44: coating the nanomaterial slurry according to a preset gradient and position.

6. The method for preparing a multi-purpose nanomaterial composite film according to claim 1, characterized in that: The S5 specifically includes the steps of: S51: Select low-temperature UV curing or plasma-assisted curing equipment, and perform preheating and debugging; S52: Set the light intensity and curing time as needed; S53: sending the substrate coated with the nanomaterial slurry into a curing device; S54: Start the curing equipment and perform the curing operation according to the preset parameters.

7. The method for preparing a multi-purpose nanomaterial composite film according to claim 1, characterized in that: The S6 specifically comprises the steps of: S61: Select additives based on the required functional strength and overall performance requirements of the composite membrane; S62: dissolving or dispersing the additive in a solvent to form an additive solution; S63: Using nano-encapsulation or in-situ polymerization, the additives are uniformly introduced into the surface or inside of the composite membrane; S64: performing subsequent treatment on the composite membrane after the additive is introduced, including cleaning and drying; S67: Test various performance indicators of composite membranes, including antibacterial properties and UV absorption properties.

8. The method for preparing a multi-purpose nanomaterial composite film according to claim 1, characterized in that: The preset functional groups include antibacterial groups and photosensitizing groups.

9. The method for preparing a multi-purpose nanomaterial composite film according to claim 7, characterized in that: The additives include antibacterial agents and ultraviolet absorbers, and the additives do not exceed 5% of the total mass of the composite film.

10. The method for preparing a multi-purpose nanomaterial composite film according to claim 2, characterized in that: The preset steps include centrifugation, washing and drying.

Citation Information

Cited By

  • High-safety nickel cobalt lithium manganate semi-solid battery and preparation method thereof

    CN119864515A